SLEEP AND MENTAL HEALTH: THE RELATIONSHIP BETWEEN SLEEP DISORDERS AND DEPRESSION - Aleksandra Anna Strzelecka; Aleksandra Ewa Basak; Sandra Khiralla-Gawlik; Agnieszka Kwiatkowska; Kinga Teper; Patrycja Świercz; Ewelina Mączka; Konrad Strużek; Wiktor Tracz (International Journal of Innovative Technologies in Social Science, 2025)
Sleep disturbances are a core feature of depressive disorders, occurring in most patients during both acute episodes and remission. Insomnia is the most prevalent form and significantly affects treatment response and relapse risk. The relationship between sleep and depression is bidirectional—sleep problems may precede, co-occur with, or result from depression. Non-pharmacological approaches such as cognitive behavioral therapy for insomnia (CBT-I) have proven effective in improving both sleep quality and depressive symptoms, especially when combined with antidepressants. Somatic interventions like chronotherapy, light therapy and sleep cycle manipulation also show promising outcomes. Recognizing and treating sleep disturbances as a primary therapeutic target can enhance the overall effectiveness of depression management and support long-term remission.